2008
DOI: 10.1016/j.juro.2007.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Identification of Interleukin-2 Therapy Response in Metastatic Renal Cell Cancer

Abstract: Introduction-To detect a predictive protein profile that distinguishes between IL-2 therapy responders and non-responders among metastatic RCC patients we used surface-enhanced laser desorption/ionization time-of-flight mass spectrometry (SELDI TOF-MS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Since then, other studies were performed with the same goal under different conditions or different proteomics approaches (3)(4)(5)(6)(7)(8). The method that was applied in this study is based on 2DE, the most traditional technology for separation of proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, other studies were performed with the same goal under different conditions or different proteomics approaches (3)(4)(5)(6)(7)(8). The method that was applied in this study is based on 2DE, the most traditional technology for separation of proteins.…”
Section: Discussionmentioning
confidence: 99%
“…A constant effort has been made (3)(4)(5)(6)(7)(8) in the search for biomarker candidates for RCC. However, none of them achieved definitive diagnostic and prognostic value in clinical practice so far.…”
Section: Introductionmentioning
confidence: 99%
“…A high-dose IL-2 trial is currently investigating its efficacy according to these predictive features to prospectively validate the selection criteria and to identify the patients likely to benefit the most from immunotherapy. A recent study based on a proteomic approach attempted to identify a new biomarker in the immunotherapy setting [56] .…”
Section: Immune Responsementioning
confidence: 99%
“…The authors identified protein differences between patients with good response to treatment and those who did not respond to treatment. The authors suggested that it is possible to avoid the undesirable side effects of treatment with IL-2 [28] .…”
Section: Rcc Versus Proteomicsmentioning
confidence: 99%